2018
DOI: 10.22159/ajpcr.2018.v11i8.27772
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Levels of Selective Oxidative Stress Markers (Malondialdehyde, Zinc, and Antioxidant Vitamins A, E, and C) in Ischemic and Non-Ischemic Heart Disease Patients Suffering From Type- 2 Diabetes

Abstract: Objective: The objective of the current study is to compare the levels of oxidative stress markers malondialdehyde (MDA), zinc, and antioxidant Vitamins (A, E, and C) in ischemic heart disease (IHD) and non-IHD patients with diabetes mellitus.Method: This is cross-sectional study group, conducted in the advanced diagnostic center (Khartoum- Sudan) from the period May 2013 to August 2015. Comprised 100 healthy subjects were, control group with mean (fasting blood sugar) 5.61=m mol/L, the age ranged from 22 to 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…11 In addition to that, the present study indicated significantly strong positive correlation between HbA1% and estimated Average glucose (r=0.78, P value =0.00) this in same with study done by Shobha. 13,14 The average plasma blood glucose corresponding to HbA1c% value of 5% is 101 mg/dl and that corresponding to mean value of 5.29% is 111 mg/dl (range for 5.29%±0.514% is 90-129 mg/dl) hence, it may be concluded that HbA1c can indeed be utilized for the monitoring of glycemic level, as a screening test, even in nondiabetic pregnancies. The correlation coefficient between HbA1c% and blood glucose is 0.80.…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition to that, the present study indicated significantly strong positive correlation between HbA1% and estimated Average glucose (r=0.78, P value =0.00) this in same with study done by Shobha. 13,14 The average plasma blood glucose corresponding to HbA1c% value of 5% is 101 mg/dl and that corresponding to mean value of 5.29% is 111 mg/dl (range for 5.29%±0.514% is 90-129 mg/dl) hence, it may be concluded that HbA1c can indeed be utilized for the monitoring of glycemic level, as a screening test, even in nondiabetic pregnancies. The correlation coefficient between HbA1c% and blood glucose is 0.80.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged use of vitamin A was also observed to reduce atherosclerosis in both animals and patients as a consequence of its antioxidant and antiinflammatory actions (Ozkanlar and Akcay, 2012;Ruiz-León et al, 2019). Supplementation of vitamin A was reported to lower the oxidative stress level in diabetic patients with ischemic heart disease (Altoum et al, 2018). Ischemia-reperfusion (I/R) induced infract size was reduced and the post-ischemic cardiac function recovery was improved by β-carotene in Zucker diabetic rats (Csepanyi et al, 2018), Furthermore, treatment with β-carotene protected the myocardium from advance glycation end productinduced SR stress, apoptosis and autophagy (Zhao et al, 2020).…”
Section: Lipo-soluble Vitamin Supplementationmentioning
confidence: 99%
“…Although data from studies with experimental animal models advocate the protective role of antioxidants versus vascular disorders [83][84][85][86], data from clinical trials are not conclusive [56,87]. For example, vitamin A has been rated as a beneficial supplement that may reduce OxS in diabetic individuals with ischemic heart disease [88]. Melatonin supplementation may reduce myocardial ischemic-reperfusion injury in male and female patients undergoing coronary artery bypass [89].…”
Section: Antioxidants On Vascular Diseasesmentioning
confidence: 99%